Intersemiotic Translation: From Medieval Poetry to Modern Movie - Leila Nik Nasab (Literary Arts, 2024)
Jacobson )1959) divides translation into three categories: intralingual, interlingual, and intersemiotic, and considers adaptation as a form of intersemiotic translation. This descriptive-analytical study aims to investigate the relationships between a classical narrative—the story of Sheikh San'an from Attar’s Conference of the Birds—and a modern movie—The Forbidden Fruit written/directed by Hassan Fathi in the 2000s. The study seeks to demonstrate, through various examples, that this movie is influenced by the story of Sheikh San'an and it is a kind of adaptation. Thus, in the process of converting the semiotic system of an ancient text into an audiovisual system, which is considered a form of intersemiotic translation, the existing intertextual relationships are decoded. The results show that, according to the classification provided by Andrew (1984) for adaptation, this intersemiotic translation is of the first type, with borrowing evident in many structural and thematic elements. In this adaptation, the filmmaker did not aim for complete fidelity to the original text, nor was its originality fully preserved. Instead, many elements of this ancient literary work were borrowed and modified to suit the constraints of the medium, cater to the preferences of the audience, and align with the objectives of the film. Keywords: Adaptation, Intersemiotic Translation, Intertextuality, Semiotic System, Sheikh San'an. Introduction Jacobson (1959, p. 16) divides translation into three categories: intralingual translation, interlingual translation, and intersemiotic translation.a) Intralingual translation, or rephrasing, involves translating verbal signs using other signs within the same language.b) Interlingual translation, or proper translation, involves translating verbal signs using another language.c) Intersemiotic translation, or transformation, involves translating verbal signs using signs from non-verbal sign systems.Andrew (1984) describes the relationship between film and text, or adaptation, in three ways: borrowing, intersection, and the fidelity of transformation. Borrowing is the most common method of adaptation, in which the content, idea, or form of a prestigious literary text is utilized. In the second type, called intersection, the original text retains much of its authenticity in the film. The third type is the fidelity of transformation, which means the reproduction of the important aspects of the original work in cinema. In this way, the original work is compared with the film. Fidelity to both the form and the spirit of the work will be considered, and aspects of the literary work will be clearly expressed in each version of the film.The following two research questions are discussed and examined in this study:In the process of intersemiotic translation from the narrative of Sheikh San'an to the screenplay of The Forbidden Fruit, what similar and different elements can be identified in the transition between these two semiotic systems?Which type of Andrew's (1984) adaptation method does The Forbidden Fruit screenplay follow in its adaptation of the story of Sheikh San'an?In Attar's works, many long and short stories can be found, which have been repeatedly adapted for the stage both inside and outside the country. Some studies have been conducted in the fields of "adaptation of Iranian literature both domestically and internationally" and "intersemiotic translation" of various texts. However, there are few, if any, studies relevant to the topic of the present study. Materials and MethodsThis study has been conducted using a descriptive-analytical method. The literary text in question is the story of Sheikh San'an, selected from the narrative section of The Conference of the Birds by Attar, and it has been compared with the screenplay of The Forbidden Fruit, directed by Hassan Fathi and shown in the 2000s. Given the scope of the study, certain structural elements such as plot, character development, beginning, ending, time, and setting, as well as thematic components like symbols, conflicts, themes, and motifs have been examined in two different semiotic systems, revealing intertextual connections. Research Findings In this intersemiotic translation from narrative to movie, given the scope of the present study, some intertextual semiotic relationships are analyzed, with greater emphasis placed on the narrative aspects of the work. The key story elements examined in this movie are as follows:Plot (narrative structure)Character and characterizationStory progressionSetting (time and place)Symbols and signsDialogueThemes and motifsThe story of Sheikh San'an, who fell in love, is one of the beautiful mystical stories, and Sheikh Farid al-Din Attar elegantly narrates it in verse in his Conference of the Birds.Most of the elements of the Sheikh San'an story can be found in The Forbidden Fruit. The tale revolves around a pious man, on the verge of old age, who suddenly, while dealing with worldly matters, distances himself from spirituality and becomes entrapped by the love of a young woman. Forced to abide by the conditions the girl sets for union, he loses everything, but in the end, with divine grace and guidance, he repents and finds the right path. In both stories, the girl ultimately attains faith. Sheikh San'an—as a religious man who has spent his life in the pursuit of religion and faith but becomes infatuated with a Christian girl—was considered an unusual tale. Similarly, in the movie, there is a scene where "Jalal", the elder son of the pious man in the story, informs his mother about his father's possible transgression. The mother, shocked and astonished, rejects his claims. Discussion of Results and Conclusion Since the narrative has manifested in the form of a movie, it naturally incorporates elements of imagination and dramatic aspects. Some events, actions, reactions, and themes are repeated in the screenplay by the filmmaker, while others have been altered in terms of the storyline and contemporary culture, and some parts have been creatively added to the script. Therefore, the different elements can be classified as follows:Addition of secondary charactersTime and setting of the storySocial and moral themesLanguage and literatureIncorporation of subplots alongside the main storyMultiplicity of characters and different conflicts It can be said that this adaptation falls under Andrew's model of "borrowing". The viewer does not witness a direct and complete adaptation of the story. The director has made an effort to ensure that the appeal of the screenplay, the audience's engagement, and the success of the movie are indebted to the elements borrowed from the tale of Sheikh San'an.